Faktor-Faktor yang Berhubungan dengan Putus Berobat Pada Penderita TB Paru BTA Positif (+ ) di Wilayah Kerja Puskesmas Harapan Raya - Khamidah .; Herlina Susmaneli (Jurnal Kesehatan Komunitas, 2016)
Dropped out of medical treatment is patients who are not medical treatment 2 consecutive months or more before the treatment done.The drop out rate treatment at puskesmas hope raya estimated to reach 40 %. This report is written in may till june 2015 . This study attempts to see if the age , sex , there is no visit pmo and the visit to the health service a factor , factors that deals in a medical treatment by those with pulmonary tuberculosis smear +. The kind of research is aimed to quantitative control observational with the design cases where taken by means of sample counting down the number of cases and control based on the data tb 01 in sample the total sample 120 consisting of 60 sample cases and 60 sample control exercised raya puskesmas hope in the work area .A measuring instrument used is the data on tb 01 .Of the data analysis to assay bivariat chi-square by test. The result of chisquare test done which is the relation of breaking up of medical treatment by age obtained pvalue 0,011 ( or = 3.500 ) , the relation of breaking up of medical treatment to the sex obtained pvalue 0,180 ( or = 1,807 ) , the relation of dropping out of treatment with no pmo obtained pvalue 0,004 ( or = 3,778 relationship and breaking up of medical treatment with a visit to health services obtained pvalue 0,001 ( or = 6,057 ). As the conclusion of this research can be said that between the ages , pmo and a visit to the whereabouts of health services is breaking up of medical treatment and risk factors chi-square test results of the sexes is not a factor of the risk of dropping out of medical treatment in people with pulmonary tuberculosis smear +. Advice for health workers to better emphasize health center for patients with pulmunory TB productive age in order to carry out the treatment to its conclusion, heving a PMO, give impetus that motivated treatment of the self.